Effect of human chorionic gonadotropin on the growth of angelfish Pterophyllum scalare (Lichtenstein, 1823 - Rajaagopalsamy, C B T; Karthikeyan, E; Venkataramani, V K (Indian Journal of Fisheries, 2016)
The influence of human chorionic gonadotropin (HCG) on the growth of the angel fish, Pterophyllum scalare (Lichtenstein,1823) was investigated in the present study. The experiment was conducted for a period of 180 days. The HCG hormonewas incorporated in pelleted feed at four different concentrations viz.,100 IU, 300 IU, 700 IU and 1000 IU per kg of feed.The control diet was prepared without HCG. The group fed with 700 IU kg-1 HCG incorporated feed attained maximumbody weight and standard mean length of 17.47 g and 69 mm respectively in 180 days of culture period. The mean standardlength, mean body weight and SGR recorded were significantly high (p